Penerapan Teknologi Sistem Tanam Pada Dua Varietas Wijen (Sesamum Indicum L.) Dengan Tipe Percabangan Yang Berbeda - Nunik Eka Diana; Eko W Widaryanto; Setyono Yudo Tyasmoro; Djumali Djumali (Buletin Tanaman Tembakau, Serat & Minyak Industri, 2021)
Tanaman wijen sebagai penghasil bahan pangan dan minyak memiliki dua tipe percabangan yaitu bercabang dan tidak bercabang. Sistem tanam yang digunakan selama ini dengan sebar sehingga produksi biji menurun. Penelitian ini bertujuan untuk mengkaji penerapan teknologi sistem tanam pada dua varietas wijen dengan tipe percabangan berbeda. Pengkajian dilakukan di IP2TP Balittas di Karangploso, Malang mulai Maret-Juni 2021.  Pengkajian ini menggunakan Rancangan Acak Kelompok menggunakan dua varietas wijen dengan tipe pecabangan berbeda dengan 6 perlakuan sistem tanam diulang sebanyak 3 kali. Parameter pengamatan meliputi tinggi tanaman, lebar kanopi, luas daun, jumlah daun, indeks luas daun, jumlah polong (kapsul) per tanaman, jumlah biji per kapsul, berat 1000 biji, produksi total dan kadar minyak. Hasil pengkajian menunjukkan bahwa penanaman varietas wijen tipe bercabang memberikan hasil produksi lebih tinggi dibanding tipe tidak bercabang. Penerapan sistem baris pada varietas wijen baik pada tipe bercabang maupun tidak bercabang terbukti memberikan peningkatan hasil dan pertumbuhan secara signifikan dibanding sistem sebar, dengan peningkatan produksi sebesar 84,6% pada varietas wijen tipe bercabang dan 46,8% pada varietas wijen tidak bercabang. Perlakuan sistem tanam baris ganda 30/90 x 25 cm pada varietas wijen tipe bercabang dan 20/60 x 25 cm pada tipe tidak bercabang cenderung memberikan hasil lebih tinggi dibandingkan perlakuan lain. APPLICATION OF PLANTING SISTEM TECHNOLOGY IN TWO VARIETIES OF SESAMUM(Sesamum indicum L.) WITH DIFFERENT BRANCHING TYPESABSTRACTSesame plants as food and oil producers have two types of branching, namely branched and unbranched. Theplanting sistem used so far is by spreading so that seed production decreases. This study aimed to examinethe application of planting sistem technology to two sesame varieties with different branching types. The studywas conducted at the IP2TP Balittas in Karangploso, Malang from March-June 2021. This study used arandomized block design consisting of 2 varieties with different branching types with six treatments of plantingsistem repeated 3 times. Parameters observed included plant height, canopy width, leaf area, number ofleaves, leaf area index, number of pods (capsules) per plant, number of seeds per capsule, weight of 1000seeds, total production and oil content. The results of the study showed that the planting branched typesesame varieties gave higher yields than the unbranched type. The application of the row sistem on sesamevarieties both on branched and unbranched types was proven to provide a significant increase in yield andgrowth compared to the spread sistem, with an increase in production of 84.6% in branched and 46.8% inunbranched type sesame variety. The double row planting sistem with plant spacing of 30/90 x 25 cm on the APPLICATION OF PLANTING SISTEM TECHNOLOGY IN TWO VARIETIES OF SESAMUM(Sesamum indicum L.) WITH DIFFERENT BRANCHING TYPESABSTRACTSesame plants as food and oil producers have two types of branching, namely branched and unbranched. The planting sistem used so far is by spreading so that seed production decreases. This study aimed to examine the application of planting sistem technology to two sesame varieties with different branching types. The study was conducted at the IP2TP Balittas in Karangploso, Malang from March-June 2021. This study used a randomized block design consisting of 2 varieties with  different branching types with six treatments of plantingsistem repeated 3 times. Parameters observed included plant height, canopy width, leaf area, number of leaves, leaf area index, number of pods (capsules) per plant, number of seeds per capsule, weight of 1000 seeds, total production and oil content. The results of the study showed that the planting branched typesesame varieties gave higher yields than the unbranched type. The application of the row sistem on sesame varieties both on branched and unbranched types was proven to provide a significant increase in yield and growth compared to the spread sistem, with an increase in production of 84.6% in branched and 46.8% in unbranched type sesame variety. The double row planting sistem with plant spacing of 30/90 x 25 cm on the branched type sesame variety and the double row sistem of 20/60 x 25 cm on the unbranched type tended togive higher yields than other treatments.